Monocytic Ontogeny of Regenerated Macrophages Characterizes the Mesotheliomagenic Responses to Carbon Nanotubes - Orsi, Micaela; Palmai-Pallag, Mihaly; Yakoub, Yousof; Ibouraadaten, Saloua; De Beukelaer, Michèle; Bouzin, Caroline; Bearzatto, Bertrand; Ambroise, Jérôme; Gala, Jean-Luc; Brusa, Davide; Lison, Dominique; Huaux, François (Frontiers in Immunology, 2021)
Macrophages are not only derived from circulating blood monocytes or embryonic precursors but also expand by proliferation. The origin determines macrophage fate and functions in steady state and pathological conditions. Macrophages predominantly infiltrate fiber-induced mesothelioma tumors and contribute to cancer development. Here, we revealed their ontogeny by comparing the response to needle-like mesotheliomagenic carbon nanotubes (CNT-7) with tangled-like non-mesotheliomagenic CNT-T. In a rat peritoneal cavity model of mesothelioma, both CNT induced a rapid macrophage disappearance reaction (MDR) of MHCIIlow resident macrophages generating an empty niche available for macrophage repopulation. Macrophage depletion after mesotheliomagenic CNT-7 was followed by a substantial inflammatory reaction, and macrophage replenishment completed after 7 days. Thirty days after non-mesotheliomagenic CNT-T, macrophage repopulation was still incomplete and accompanied by a limited inflammatory reaction. Cell depletion experiments, flow cytometry and RNA-seq analysis demonstrated that, after mesotheliomagenic CNT-7 exposure, resident macrophages were mainly replaced by an influx of monocytes, which differentiated locally into MHCIIhigh inflammatory macrophages. In contrast, the low inflammatory response induced by CNT-T was associated by the accumulation of self-renewing MHCIIlow macrophages that initially derive from monocytes. In conclusion, the mesotheliomagenic response to CNT specifically relies on macrophage niche recolonization by monocyte-derived inflammatory macrophages. In contrast, the apparent homeostasis after non-mesotheliomagenic CNT treatment involves a macrophage regeneration by proliferation. Macrophage depletion and repopulation are thus decisive events characterizing the carcinogenic activity of particles and fibers.